Incidence of osteoporotic fractures in elderly women and men in Finland during 2005–2006: a population-based study. (September 2014) - Koski, A-M.; Patala, A.; Patala, E.; Sund, R.
Background and Aims: Osteoporosis is a major health concern in elderly population. Low-trauma fractures offer one way of identifying these patients for treatment. Population-specific incidences of osteoporotic fractures are essential to validate tools for clinical decision making. Material and Methods: To evaluate population-based osteoporotic fracture incidences in Central Finland, we performed a manual search of low-trauma fractures 2005–2006 from the records of all the local health-care organizations treating trauma patients. We identified low-trauma fracture patients from radiology reports from five health centers serving the inhabitants of nine municipalities and from the patient records of two hospitals in Central Finland. The manually collected data were then compared against data from the Finnish Health Care Register. Results: The crude incidence of all osteoporotic fractures in 2005–2006 in the population aged 50 years was 1254/100, 000 person years: 694/100, 000 person years in men and 1718/100, 000 person years in women. Fracture numbers derived from register data were similar to those manually collected for hip and humerus fractures, but clearly smaller than those for wrist and ankle fractures. Conclusions: Population-based low-trauma fracture incidences, reported here for Finland, constitute a basis for calibration of fracture risk evaluation tools (e.g. the World Health Organization fracture risk evaluation tool, FRAX). This study showed that register data underestimate the incidences of, in particular, distal radius and ankle fractures.